MOBILITAS ULANG - ALIK PENDUDUK NAGARI KINARI KECAMATAN BUKIT SUNDI KABUPATEN SOLOK - sari, sildila sari dila; Iskarni, Paus (DEPARTEMEN GEOGRAFI FIS UNP, 2024)
Abstract This study aims to find out about (1) Characteristics (2) Push and pull factors (3) How is the direction of the destination location, distance traveled, mode of transportation, transportation costs and travel time (4) Socio-economic conditions of shuttle mobility actors in Nagari Kinari sub-district Sundi Hill, Solok Regency, West Sumatra Province. This type of research is Mix Methods. The analysis technique uses the percentage formula. The results of the study (1) of the population who carry out roundtrip mobility are dominated by women, and of productive age, education is the dominant actor in elementary school. (2) the factors that encourage residents to do mobility are the difficulty of getting a job in the area of ​​origin and the wages in the area of ​​origin are low. The pull factor is wider and varied job opportunities, the wage rate is higher. the distance to the mobility location is about 32 km, the mode of transportation used by motorists and angkot mobility actors, the transportation fee is Rp. 5000 – 10,000. The travel time for roundtrip mobility is 1 – 1 hours. (4) economic conditions, namely the livelihood of roundtrip mobility in the dominant farm laborers, the dominant income is Rp. 2,040,000 - 4,800,000. own dominant home ownership. Keywords: characteristics, push and pull factors, socio-economic conditions